URGENSI PENGATURAN UNDANG-UNDANG PASAR FISIK ASET KRIPTO (CRYPTO ASSET) - Krisnawangsa, Hans Christoper; Hasiholan, Christian Tarapul Anjur; Adhyaksa, Made Dharma Aditya; Maspaitella, Lourenthya Fleurette (Dialogia Iuridica, 2021)
Crypto Assets is a new alternative investment concept in Indonesia. The legal basis for regulating crypto assets currently in force in Indonesia cannot accommodate the development of the Crypto assets concept which continues to undergo significant changes. The physical market for crypto assets is incompatible when regulated by the provisions of Law Number 32 of 1997 on commodity futures trading and its amendments, namely Law Number 10 of 2011 because the physical market has conceptual differences with the provisions of the futures market in general. The object traded in the physical market is the commodity, while in the commodity futures market the object is futures contracts (and their derivatives) for commodities traded in the physical market. The scope of the commodity futures market as regulated in Article 1 of the Commodity Futures Trading Law does not accommodate commodity trading in the physical market. The urgency of regulating the physical market for crypto assets with a separate law is the implementation of the principle of legal certainty and protection of crypto asset investors. The method used in writing this journal is normative research using books, journal references, and laws and regulations that are relevant to the legal issues in this study. The results of this study indicate that the regulation of the physical law on crypto assets is needed because crypto assets should be regulated into two separate arrangements so that it is not appropriate if the regulation regarding crypto assets is only accommodated by the Commodity Futures Trading Law.